Imagining Jihad. Issue 4 (7th August 2016) - Barbato, Mariano; Hantscher, Sinja; Lederer, Markus
Abstract : The article examines how the Islamic State (IS) has evolved into a community- and initial state-building project. Using Benedict Anderson's concept of "imagined community" (Anderson, B. [1983]. Imagined communities . London: Verso), we claim that IS is about to construct an aggressive Sunni national identity with a specific territorial claim, which could have a high impact on international order. Comparing nationalism and Islamism allows us to understand the strong appeal of the latter much better than a focus on religion alone.